The Role of Mixed Convection and Hydrodynamic Dispersion During CO2 Dissolution in Saline Aquifers: A Numerical Study. Issue 3 (7th March 2022) - Tsinober, Avihai; Rosenzweig, Ravid; Class, Holger; Helmig, Rainer; Shavit, Uri
Abstract: Dissolution trapping plays a significant role in CO2 geological storage. When CO2 dissolves in aquifer brines, the aqueous solution is heavier than the underlying resident brine. This results in convective instability in the form of CO2 ‐rich fingers, which accelerates dissolution. It was recently shown that background flow affects CO2 dissolution by suppressing the development of convective fingers. However, there was a discrepancy between computational results and measurements, with the computational results demonstrating a decrease in the dissolution rate and the laboratory measurements showing no significant effect. Here, we attempted to understand this difference by exploring the relations between the transport mechanisms that facilitate convective mixing. We investigated the role of background flow by using numerical simulations that were validated by laboratory measurements and analytical solutions. Simulations were generated for the same porous medium and fluid pair used in the experiments, keeping the Rayleigh number constant, while changing the background velocity and the Peclet number. Studying the flux components revealed three distinct regimes characterized by the Peclet to Rayleigh ratio Pe / Ra . When Pe / Ra  < 0.77, natural convection dominated, and dissolution remained approximately constant. When the background flow was large ( Pe / Ra  > 2), dissolution was controlled by pure forced convection and increased with Pe / Ra . In the intermediate range (0.77 <  Pe / Ra < 2), both natural convection and forced convection were important. Key Points: We investigate the effect of background flow and hydrodynamic dispersion on convective dissolution using numerical simulations Results confirm that the dissolution flux is invariant within a certain range of velocities in accordance with previous experimental results We demonstrate a tradeoff between natural convection and the sum of forced convection and the associated dispersive flux